Preface: 5th International Conference on Materials Science, Resource and Environmental Engineering (MSREE 2023) - Liu, Qingwei; Jefferson, Willie (Transactions on Environment, Energy and Earth Sciences, 2024)
This proceeding includes original and peer-reviewed research papers from the 5th International Conference on Materials Science, Resource and Environmental Engineering (MSREE 2023: http://www.msree.org), held on December 16-17, 2023 in Xi’an, China. The MSREE 2023 conference had three main topics: 1. Material Science and Engineering Applications; 2. Energy Science and Power Engineering; 3. Resource and Environmental Engineering. The aim of MSREE 2023 is to provide a platform for researchers, engineers, and academicians, as well as industrial professionals, to present their research results and development activities in materials science, energy technology, power engineering. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration. 5th MSREE received 72 submissions while 4th MSREE received 216 manuscripts. And 17 of them had been accepted by our reviewers in 5th MSREE while 85 papers in 4th MSREE. By submitting a paper to MSREE 2023, the authors agreed to the review process and understood that papers undergo a peer-review process. Manuscripts were reviewed by appropriately qualified experts in the field selected by the Conference Committee, who gave detailed comments and-if the submission was accepted the authors would submit a revised version that took into account this feedback. All papers were reviewed using a double-blind review process: authors declared their names and affiliations in the manuscript for the reviewers to see, but reviewers did not know each other’s identities, nor did the authors receive information about who had reviewed their manuscript. The Committees of MSREE 2023 invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit. Qingwei Liu, Willie Jefferson Xi’an, China